2019
DOI: 10.1097/md.0000000000015947
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of fatigue with other disease related and psychosocial factors in patients with rheumatoid arthritis treated with tocilizumab

Abstract: To assess the hypothesis if tocilizumab (TCZ) is effective on disease activity, and also its effect in fatigue and other clinical and psychological disease-related factors in patients with rheumatoid arthritis (RA) treated with TCZ. A 24-week, multicenter, prospective, observational study in patients with moderate to severe RA receiving TCZ after failure or intolerance to disease-modifying antirheumatic drugs or tumor necrosis factor-alpha was conducted. Of the 122 patients included, 85 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
0
17
0
2
Order By: Relevance
“…Virtually all treatments in RA will reduce fatigue, including conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), targeted synthetic DMARDs, biologic DMARDs and corticosteroids. 37 39–54 The average effect of treatment on fatigue in active RA with various advanced therapies is meaningful but not large. 39 Treatment of disease activity in RA has a small impact on fatigue, whereas physical inactivity, poor sleep and depressed mood explain most of the fatigue.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually all treatments in RA will reduce fatigue, including conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), targeted synthetic DMARDs, biologic DMARDs and corticosteroids. 37 39–54 The average effect of treatment on fatigue in active RA with various advanced therapies is meaningful but not large. 39 Treatment of disease activity in RA has a small impact on fatigue, whereas physical inactivity, poor sleep and depressed mood explain most of the fatigue.…”
Section: Treatmentmentioning
confidence: 99%
“…46 The variance in fatigue in a tocilizumab treatment study was explained mostly by sleepiness, depressive symptoms and disease activity (DAS28). 47 In RCTs, sarilumab has shown improvement in PROs, with an effect size that was clinically relevant for fatigue but not as large as for pain. 48…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, Corominas et al reported through a multicenter study that Tocilizumab, received failure or intolerance to DMARDs or TNF inhibitor, significantly improved fatigue in RA. Sleepiness, depression and DAS28 were the parameters identified as factors explaining fatigue variance with the use of Tocilizumab in RA patients [26]. This may be due to multifactorial, complex and not clearly understood fatigue which also explains the difficulty of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies suggest that fatigue is not related to the disease activity but would be especially associated with pain in functional status and especially with other symptoms such as sleep disorders, anxiety and depression [26][27][28][29][30]. Recently, Corominas et al reported through a multicenter study that Tocilizumab, received failure or intolerance to DMARDs or TNF inhibitor, significantly improved fatigue in RA.…”
Section: Discussionmentioning
confidence: 99%
“…There is a known relationship between increased levels of pro-inflammatory IL-6 and the risk of depression [33]. It is no wonder then that research indicates the combined effects of tocilizumab not only on RA but also on depression [34]. However, there is also a voice from experts who says that taking tocilizumab may not be an appropriate therapeutic goal in the treatment of depression [35], so opinions are somewhat divided.…”
Section: Tocilizumabmentioning
confidence: 99%